Methodological proposal for mapping non-forest areas presents in the project of deforested areas of the Brazilian Legal Amazon (Research, Society and Development, 2022)
The areas with non-forest formations present in the Brazilian Legal Amazon are under threat due to the increase in deforestation associated with agriculture, pastures, road infrastructure and the population increase of cities and settlements. However, its diversity of vegetation physiognomies and its conservation status are still little known. This research presents a methodological proposal for mapping areas with non-forest formations, based on a better understanding of the dynamics of use and coverage of the Amazon region, following the classes of the TerraClass Project. The study was conducted in a localized area of the state of Rondônia and was proposed to perform landscape analysis through remote sensing and geoprocessing techniques using the Google Earth Engine platform for the year 2019. The results reveal a change in the landscape, where the classes Pasture, Forest and Non-forest make up most of the landscape of the area. The land use data generated from the processing of satellite images and the crossing of non-forest polygons showed that the Pasture and Forest classes began to make up most of the landscape where it should have only the presence of non-forest. It is emphasized the importance of continuing the mapping of the dynamics of landscape changes that ensure the conservation of areas of non-forest remnants given intensity with which changes occur in the region.